Cognitive Predictors of Word and Pseudoword Reading in Spanish First-Grade Children - González-Valenzuela, María J.; Díaz-Giráldez, Félix; López-Montiel, María D. (Frontiers in Psychology, 2016)
The study examines the individual and combined contribution of several cognitive variables (phonemic awareness, phonological memory, and alphanumeric and non-alphanumeric rapid naming) to word and pseudoword reading ability among first-grade Spanish children. Participants were 116 Spanish-speaking children aged six years and without special educational needs, all of whom were attending schools in a medium socioeconomic area. Descriptive/exploratory and bivariate analyses were performed with the data derived from three measures of reading ability (accuracy, speed, and efficiency), and hierarchical multivariate regression models were constructed. In general, the results confirm that, with the exception of non-alphanumeric rapid naming, the cognitive variables studied are predictors of reading performance for words and pseudowords, although their influence differs depending on the reading measures and type of linguistic unit considered . Phonemic awareness, phonological memory, and alphanumeric rapid naming were the best predictors of reading accuracy for words and pseudowords. Variability in the other two measures of reading ability (speed and efficiency) was best explained by alphanumeric rapid naming. These results suggest that reading is a complex skill that depends on different types of cognitive variables according to the age and/or level of the reader, the type of orthography and the type of measure used. Furthermore, they highlight the need to provide instruction in these processes from an early age so as to address or prevent the problems that children may present.